Coupled quadratic boost converter for stand-alone PV applications - Chakraborty, Suvamit; Umarikar, Amod C. (Institute of Advanced Engineering and Science, 2024)
This study focuses on a stand-alone photovoltaic (PV) system employing a high step-up quadratic boost converter and a battery management system. The quadratic boost converter, featuring a tapped inductor, facilitates voltage boosting by adjusting the duty ratio, ensuring low voltage stress on the active switch and enhancing overall efficiency. Coordination control techniques are proposed for smooth power transfer between the PV array, battery, and DC-link, accommodating variations in solar irradiation, ambient temperature, and loads. Design, modeling, and simulation are conducted using the PLEXSIM platform, and a real-time laboratory prototype validates system performance. This integrated approach establishes the feasibility and effectiveness of the proposed system, offering a robust framework for off-grid or rural electrification applications with its ability to operate at low voltage levels, efficient power transfer, and stable performance under uncertain conditions.